2019
DOI: 10.1155/2019/1287968
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Strategy for New Products with Presales

Abstract: An increasing number of firms and retailers use presale strategies to induce customers to purchase before new products enter the market to increase their market share. Presales have gradually become a hot issue in business and academic circles. Based on a skimming pricing strategy and a penetration pricing strategy, this paper uses the different choice behaviors of two types of consumers to investigate the pricing strategy of preselling new products. The results show that if the proportion of fashion consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…e results showed that for a DCR, the best brand strategy is to adopt as many brand differences as possible between the online and offline stores, especially when consumers are less price sensitive and the market base is larger. With an increasing number of retailers adopting dual channels, scholars have deeply investigated the decisionmaking issues facing DCRs from different perspectives, including competitive pricing [66][67][68][69], channel conflicts and coordination [70][71][72], and channel strategy [73][74][75]. In addition, some scholars have studied the business strategies of DCRs, such as the POPU (preorder-online, pickup-instore) strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e results showed that for a DCR, the best brand strategy is to adopt as many brand differences as possible between the online and offline stores, especially when consumers are less price sensitive and the market base is larger. With an increasing number of retailers adopting dual channels, scholars have deeply investigated the decisionmaking issues facing DCRs from different perspectives, including competitive pricing [66][67][68][69], channel conflicts and coordination [70][71][72], and channel strategy [73][74][75]. In addition, some scholars have studied the business strategies of DCRs, such as the POPU (preorder-online, pickup-instore) strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the implementation of the presale strategy, the seller can identify the segment of consumers who are willing to pay a premium for early delivery and the segment of consumers who choose to wait for a low price but may face shortage risk; then, the seller can formulate a differential pricing strategy to maximize sales. In addition, the presale strategy can allow the seller to secure some revenue in advance [8], reducing the possibility of other problems caused by a shortage of funds. Furthermore, the presale strategy can be combined with ordering strategy [1], innovation strategy [9] and refund strategy [10,11] to support the operations of enterprises and improve their competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a presale option, whether strategic consumers accept the seller's presale strategy depends on the net utility obtained from the purchase of presale products. Following Feng, et al [8], we define the net utility that a consumer derives from purchasing a product (including presale and spot sale) as the valuation of the product minus the costs paid for the product, including prices and other opportunity costs. However, unlike Feng, et al [8], we find that the net utility a consumer obtains from purchasing a product is also related to the seller's sales efforts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations